Child-Rearing Methods and Their Impact on Toddler Nutritional Status - Nuzula, Firdawsyi; Nurfazriah Oktaviana, Maulida (Poltekkes Kemenkes Surakarta, 2024)
Background: Child-rearing methods can influence the prevalence of stunting and wasting in toddlers because parental care plays a crucial role in the availability of food sources consumed by toddlers daily. Additionally, parents are the individuals closest to the growth and development of their children. The aim is to analyze the influence of the child-rearing methods reinforcement on nutritional status. Methods: Analytical observational research type with a cross-sectional design using a total sampling technique with 50 respondents. Data collection using a questionnaire. ANOVA Multiple Linear Regression Test. Results: The results of the analysis show that implementing feeding practices influences nutritional status, with a p-value of 0.007. There is no influence of psychosocial stimulation on children's nutritional status, with a p-value of 0.086. Healthcare practices influence nutritional status, with a p-value of 0.003. The ANOVA test results with an R square value of 0.080 conclude that the independent variable affects the dependent variable by 8%, while other factors influence the remaining 92%. The regression analysis results for the implementation of feeding practices show a p-value of 0.297, psychosocial stimulation shows a p-value of 0.789, and healthcare practices show a p-value of 0.444, indicating that none of these three variables influences children's nutritional status. Conclusion: The role of the family contributes significantly and fundamentally to a child's overall growth and development. The involvement and activity of mothers in nutritional status is an effort to prevent diseases, such as regularly taking their children for complete basic immunizations and providing healthcare.